Development of 3-D Finite Element Models for Geo-Jute Reinforced Flexible Pavement - Md Mostaqur Rahman; Sajib Saha; Amin Sami Amin Hamdi; Md Jobair Bin Alam (Salehan Institute of Higher Education, 2019)
In this study, three dimensional (3-D) finite element analysis are performed to evaluate the effect of geo-textile interlayer on the performance of flexible pavement. The main objective of this study is to evaluate the improvement in stress distribution of flexible pavement due to the application of geo-jute at three specific positions i.e., subgrade-base interface, base-asphalt layer interface, and within asphalt layers. Stress, strain and displacement values are investigated and compared for the application of geo-jute interlayer on various positions. Moreover, to better understand the mechanistic behavior of geo-jute on pavement subgrade, a separate 3-D finite element model is developed to simulate the California bearing ratio (CBR) test on geo-jute reinforced soil. Results showed that the inclusion of geo-jute on flexible pavement significantly improves the pavement performance by producing lower stress, strain, and displacement at top of the subgrade. Moreover, the bearing capacity of subgrade soil increased more than 20% due to the inclusion of geo-jute.